Measurement of Environmental Performance Indicators for Ikm Batik "Ka" Rembang Using Iepms, Ahp and Omax Methods - Nuzulia Khoiriyah; Wiwiek Fatmawati (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2019)
Environmental performance evaluation of IKM Batik KA is carried out by combining 3 methods: Integrated Environment Performance Measurement System (IEPMS), Analytical Hierarchy Process (AHP) and Objective Matrix (OMAX). Of the 32 Key to Environment Performance Indicators (KEPI) submitted to IKM, 18 quantitative indicators and 14 qualitative indicators were selected to be assessed. All KEPI have almost the same importance in the range of 0 - 10%. The results of calculations with OMAX and the Traffic light system assessment show that there are 6 KEPI at the green level, 2 KEPI at the yellow level and 18 KEPI at the red level. There are only 2 KEPI, namely indicators I2 and D1 which have a high level of importance and are at the green level, which means that the desired targets and achievements are synchronized. The total achievement value of KEPI in the OMAX calculation is at 3.31, it is included in the red category, meaning that the environmental performance of the KA Batik IKM is still bad and must be corrected immediately.